Dental fluorosis and oral health status of 13-15-Year-Old school children of Chikkaballapur District: A cross-sectional study - Punith Shetty; A Shamala; R Murali; Y Mansi; Roomani Srivastava; Arpan Debnath (Wolters Kluwer Medknow Publications, 2017)
Introduction: The high prevalence, severity, and the crippling nature of oral diseases lead to significant absenteeism in schools and economic loss in the working population. Dental fluorosis is endemic in 15 states of India and Chikkaballapur district is one among them. Aim: To assess dental fluorosis and oral health status and in Chikkaballapur district among 13-15 years school going children. Materials and Methods: A cross-sectional study was conducted among 2400 school going children of 13-15-year-old in Chikkaballapur district. The data regarding the dental fluorosis were collected using the Thylstrup and Fejerskov index. The clinical examination for the oral health status was determined using the WHO Oral Assessment Form 1997. Proportions were compared using Chi-square test, and one-way analysis of variance was used to test the differences. Results: It was seen that the mean decayed, missing, and filled teeth was highest among the 13-year-old at 1.39. Bleeding on probing and calculus was highest among 15-year-old with 83.5% and 84.6%, respectively. The prevalence of dental fluorosis in Chikkaballapur district was found to be 41.1%. Conclusion: The oral health status of the individuals was poor, and the prevalence of fluorosis was high. There is a need to create awareness regarding oral health and fluorosis.